REGULARITY AND NUMERICAL SOLUTION FOR THE EXACT CONTROL - Rincon, Mauro Antonio (1999)
In this paper we study a Numerical Method based on Finite Difference to the Boundary Exact Controllability problem for the Wave Equation. We consider the one dimensional problem. A regularity result is pro ven in order to allow us to use the Finite Difference Method. Numerical results are shown and compared to the exact solution of some particular problems, computed by the Fourier Serie.